First record of Trichogramma pretiosum parasitizing Iridopsis panopla eggs in eucalyptus in Brazil - Santos, Fernando Henrique Moreira dos; Pereira, Fabricio Fagundes; Cardoso, Carlos Reinier Garcia; Lucchetta, Jessica Terilli; Santos, Juliana Pereira; Ramos, Luciano Flavio Neves; Dias, Lucas de Souza; Araujo, Heloisa Martins de; Silva, Nadja Nara Pereira da [UNESP]; Wilcken, Carlos Frederico [UNESP]; Santos, Fabio Araujo dos [UNESP] (Walter De Gruyter Gmbh, 2024)
Iridopsis panopla Prout (Lepidoptera: Geometridae) is an important lepidopteran defoliator of eucalyptus. I. panopla eggs were collected naturally in a commercial plantation of Eucalyptus urograndis W. Hill (Myrtaceae) in Tr & ecirc;s Lagoas, Mato Grosso do Sul, Brazil. After nine days, the natural emergence of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) occurred from I. panopla eggs. Parasitism was evaluated under laboratory and field conditions, this being the first record for eucalyptus in Brazil. Based on the biological characteristics evaluated in the laboratory, I. panopla eggs are suitable for T. pretiosum reproduction. The obtained percentage parasitism, particularly when 72,000 adult females of T. pretiosum per hectare were employed, provide valuable insights regarding the potential of T. pretiosum as an effective biological control agent against I. panopla in eucalyptus plantations.
Keywords: biological control; lepidopteran pests; Eucalyptus urograndis; parasitism evaluation; pest management